Open access megajournals: The publisher perspective (Part 2: Operational realities). Issue 4 (4th September 2017) - Wakeling, Simon; Spezi, Valérie; Creaser, Claire; Fry, Jenny; Pinfield, Stephen; Willett, Peter
Abstract : This paper is the second of two Learned Publishing articles in which we report the results of a series of interviews, with senior publishers and editors exploring open access megajournals (OAMJs). Megajournals (of which PLoS One is the best known example) represent a relatively new approach to scholarly communication and can be characterized as large, broad‐scope, open access journals, which take an innovative approach to peer review, basing acceptance decisions solely on the technical or scientific soundness of the article. Based on interviews with 31 publishers and editors, this paper reports the perceived cultural, operational, and technical challenges associated with launching, growing, and maintaining a megajournal. We find that overcoming these challenges while delivering the societal benefits associated with OAMJs is seen to require significant investment in people and systems, as well as an ongoing commitment to the model.